Active and passive biosorption of Pb(II)using live and dead biomass of marine bacterium Bacillus xiamenensis PbRPSD202: Kinetics and isotherm studies. (1st October 2019) - Mohapatra, Ranjan Kumar; Parhi, Pankaj Kumar; Pandey, Sony; Bindhani, Birendra Kumar; Thatoi, Hrudayanath; Panda, Chitta Ranjan
Abstract: A highly lead(II) resistant (up to 2200 mg/l) bacterium PbRPSD202 was selected among 210 lead resistant bacteria isolated from marine environment of Paradeep Port, Odisha for possible biosoption of toxic Pb (II) ions from metals polluted environments. The bacterium was identified as Bacillus xiamenensis following the phenotypic as well as 16S rRNA gene sequence analysis. In addition to Pb(II), it also showed resistance towards other heavy metals like Cd(II), Cr(VI), As(III), Cu(II), Ni(II) and Zn(II). Batch biosorption of Pb(II) using both live and dead biomass of this strain was investigated under different operational parametric conditions such as pH, temperature, NaCl concentration, shaking speed, treatment time, biomass concentration and initial Pb(II) concentration. The maximum Pb(II) uptake of 216.75 and 207.4 mg/g biomass was obtained with live and dead biomass, respectively, at the optimum condition (4% w/v NaCl, pH 6.0, 35 °C, 140 rpm and 1 g/l biosorbent dose). Both active as well as passive Pb(II) bio-sorption process showed best fit with the pseudo-second-order kinetic model. The sorption mechanism was favoured with Langmuir isotherm model indicating monolayer type adsorption. FTIR and FESEM-EDX analysis further ensured the possible interactions of Pb(II) with bacterial cell surface ligands like hydroxyl, carbonyl, carboxyl and amine groups during surface adsorption. TEM analysis revealed the intracellular accumulation of lead ions. This investigation highlights the potential application of this bacterium for bioremediation of lead(II) from the multiple metals contaminated saline environment through biosorption. Graphical abstract: Image 1 Highlights: Isolated B. xiamenensis PbRPSD202 is a noble marine Pb(II) resistant bacterium. This strain is also found to be an efficient multiple metal resistant bacteria. Isotherm study ensured the effective loading of Pb(II) on the bacterial biomass. Maximum Pb(II) loading capacity of live and dead biomass was 216.75 and 207.4 mg/g. TEM & SEM analysis ascertained the extra- and intra-cellular accumulation of Pb(II).